KARL GOOSS AND A TEMPLE OF JUPITER IN APULUM - Csaba Szabó (Journal of Ancient History and Archaeology)
Karl Gooss (1844-1881) was one of the few intellectuals of his time who witnessed personally the building of the railway and the ditch of Alba Iulia between 1865 and 1868. The construction was the biggest project of the city since the building of the Vauban fort and destroyed the most significant part of the Colonia Aurelia Apulensis, one of the biggest urban centers of the province. During these works, Gooss witnessed the discovery and destruction of the first Jupiter temple attested in Dacia, the biggest silver deposit ever found in Transylvania and the first coin hoard of Apulum. His German publication was ignored by the later historiography, although it is the first and only detailed account of the archaeological finds discovered in the Partoș in the end of August, 1867. His detailed account helps us to identify the context of some well known artifacts and to reconsider the topography of the Colonia Aurelia Apulensis.